Wujud Kepedulian Kelompok PKM Farmasi Melalui Penyuluhan untuk Meningkatkan Kesadaran Siswa dalam Menerapkan Pola Hidup Bersih dan Sehat: The Manifestation of Concern by the Pharmacy PKM Group Through Counseling to Increase Students' Awareness in Implementing Clean and Healthy Lifestyle - Perdana, Farid; Juliani, Nining; Sukma, Annisa Putri; Nurulhuda, Siti Salwa; Hasanah, Mutia Aas; Junaedi, Jujun; Febryanti, Mhutia Shalsila; Fitriyani, Sinta; Nurhayati, Ade; Lubis, Novriyanti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This outreach activity for students was held by SMP Plus Sukaraja Garut, and aimed at increasing students' awareness about the importance of Clean and Healthy Living Behavior (PHBS), especially regarding adequate water intake and regular exercise. The method used in this outreach is through the distribution of brochures and direct presentations at one of the schools in the Garut Regency. Counseling is carried out by providing a pretest and posttest to measure students' level of understanding. The results of this activity show that using brochures as an information medium is quite effective because they can be read repeatedly and the direct presentation here allows for two-way interaction to clarify understanding. This counseling succeeded in increasing students' knowledge and awareness about the importance of PHBS, water intake, and exercise by 78.85%. It is hoped that this PKM activity can encourage students to implement healthy living habits sustainably.